2001
DOI: 10.2466/pr0.2001.88.3.651
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in Late Adulthood

Abstract: MacDonald's Expressions of Spirituality Inventory was used to examine spirituality in late adulthood using a sample of 30 people (22 women, 8 men) whose mean age was 72.6 yr. While average scores are higher on scales measuring spiritual and religious beliefs and practices for the sample than for a standardization group of undergraduate students with a mean age of 21.0 yr., means are lower on scales measuring paranormal beliefs. Low scores on death anxiety are correlated only with Existential Well-being and age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…In fact, older adults as a group appear to be more involved in religious and spiritual activities. For instance, Heintz and Baruss (2001) Spirituality Inventory and found that older adults scored higher on nearly all indices of spirituality compared to younger adults. However, Ingersoll-Dayton and colleagues (Ingersoll-Dayton, Krause, & Morgan, 2002) studied religious trajectories and transitions over the life course and found that many older adults, in response to an adverse event, changed their spiritual and religious trajectory accordingly.…”
mentioning
confidence: 97%
“…In fact, older adults as a group appear to be more involved in religious and spiritual activities. For instance, Heintz and Baruss (2001) Spirituality Inventory and found that older adults scored higher on nearly all indices of spirituality compared to younger adults. However, Ingersoll-Dayton and colleagues (Ingersoll-Dayton, Krause, & Morgan, 2002) studied religious trajectories and transitions over the life course and found that many older adults, in response to an adverse event, changed their spiritual and religious trajectory accordingly.…”
mentioning
confidence: 97%
“…Past research has suggested that as an individual ages, his/her spiritual and religious beliefs and practices become more frequent and important (Heintz & Baruss, 2001). One's concern for the environment may be associated with one's spirituality and belief system, as is seen in Eastern traditions, and therefore as one ages his/her care for the environment may increase as well.…”
mentioning
confidence: 98%
“…However, older adults may be particularly adept at utilizing spiritual resources. For example, Heintz and Baruss (2001) examined spiritual characteristics between older and younger adults. Their analysis revealed that the older sample scored higher in all areas of spiritual expression except paranormal beliefs.…”
mentioning
confidence: 99%